Streamlined percutaneous atrial septal defect closure in adults - Arı, Selma; Ari, Hasan; Can, Veysi; Çamcı, Sencer; Melek, Mehmet (The European Research Journal, 2020)
Objectives: The aim of the study to evaluate the safety and efficacy of the transthoracic echocardiography (TTE) guided secundum atrial septal defect (ASD) closure without balloon sizing, sedation or general anesthesia in adults. Methods: We retrospectively evaluated 200 secundum ASD closure patients in the tertiary cardiology center. Transesophageal echocardiography (TEE) was performed to all the patients at least one day before the intervention by the procedure operators. The patients who were closed with a cribriform device, using more than one device, with insufficient rim (<5 mm) (other than the anterior superior rim (aortic rim)), totally flail, and complex interatrial septum anatomy were excluded from the analysis.The size of the ASD closure device was chosen according to the largest diameter measured by TEE. ASD device was selected as 4 mm larger in patients without anterior superior rim and 2 mm larger in other patients than the largest diameter measured in 2D-TEE. Results: In the remaining 166 patients, the procedure was performed with TTE and fluoroscopy guidance without balloon sizing, sedation or general anesthesia. The procedure was performed through right femoral vein. The patients age: 38.56 ± 14.72, gender: 57 male, 109 female, ASD size: 18.88 ± 5.99 mm, anterior superior rim: 5.30 ± 4.04 mm, anterior inferior rim: 14.22 ± 6.46 mm, posterior superior rim: 17.16 ± 4.96 mm, posterior inferior rim: 16.67 ± 7.48 mm. ASD device size: 23.74 ± 6.59 mm. The procedure success rate was 98.1% (163 patients). The complications; 1 patient device embolised, 2 patients device was not placed in the correct position by TTE. Conclusions: TTE and fluoroscopy-guided secundum ASD closure without balloon sizing, sedation or general anesthesia by experienced operators is a safe and effective procedure.